PENGARUH MOTIVASI, KOMPENSASI DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA PT. GIGA NUSANTARA - Nuriman Baruhu; Ananda Fitriani Dwi (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted on employees of PT Giga Nusantara. This study aims to determine the effect of motivation, compensation, and commitment to employee performance. In this study the data was collect with a tool in the form of observation, interviews and questionnaires to 110 respondenst with purposive sampling technique, which aims to determine respondents perceptions of each variable. The analysis used includes data instrument test (validity test, reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), and hypothesis testing (F test, t test, coefficient of determination). From the result of the analysis using regression can be seen that the variable of motivation, compensation, and commitment, all have a positive effect on employee performance. From the t test, the result of motivation, compensation, and commitment are obtained, which have a significant partial effect on employee performance.